Flexible and stretchable touchpad - Tay, Kai Wen (Nanyang Technological University, 2022)
Flexible and stretchable wearable technology needs to be developed in order to broaden the range of applications. This study aims to create a flexible and stretchable touchpad prototype that can be incorporated into clothing.